PHARMACY PRACTICE SITES OF PHARMACISTS AND PHARMACY TECHNICIANS IN AL-DHALEA GOVERNORATE, YEMEN: A CROSS-SECTIONAL STUDY - TAREQ MAQLAM; ABDULLAH H MAAD; MOHAMMED ALI AHMED SAEED; MOHAMED JAMAL QASIM; ABBAS ABDULRIDHA MEHIHI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to identify the practice sites of the pharmacists and pharmacy technicians in Al-Dhalea governorate. Methods: A cross-sectional analytical study was designed to identify pharmacy practice sites of pharmacists and pharmacy technicians in Al-Dhalea governorate. A total of 227 pharmacists and pharmacy technicians were evaluated for their pharmacy practice sites from June to July 2023. Data were collected by a questionnaire that obtained their information through face-to-face interviews with pharmacists and pharmacy technicians. Data were processed by computer facilities through the program Statistical Package for the Social Sciences. Results: The results showed that the most common pharmacy practice site was the community pharmacy, with a total percentage (49.5%), and the most common reason for choosing this practice site was due to desire. For the hospital pharmacy site, it was 24.5%, and also for a desired reason. Then in marketing, with a total of 23.5%, the most common reason was due to financial purpose, whereas the lowest common pharmacy practice sites were in academic institutions, with 7.0% and the most common reason was desire. Then the management field (3.5%). In addition, 5.5% of the respondents were working in non-pharmacy practice sites, and the most common reason was due to insufficient wages. Statistically significant associations were found between qualification and practice site (p<0.001), as well as between specific reasons and site choice – community pharmacy (p<0.002), hospital pharmacy (p<0.001), marketing (p<0.001), management (p<0.003), academic (p<0.001), and non-pharmacy sites (p<0.001). Conclusion: Pharmacy technicians outnumbered pharmacists in community pharmacies, hospital pharmacies, and management positions. Conversely, pharmacists were more prevalent than technicians in marketing and academic settings. This distribution suggests differing workforce demands across pharmacy sectors in the region. However, the short duration of data collection (8 weeks) may limit the ability to assess long-term trends or seasonal fluctuations in pharmacy employment patterns.